Studi Stabilitas Peralihan di Sistem Pembangkit Listrik Tenaga Disel Merawang - Asyari, Hasyim; Asmar; Sunanda, Wahri (ELECTRON Jurnal Ilmiah Teknik Elektro, 2022)
The Merawang diesel power plant (PLTD) as one of the generating units in the Bangka area, the Bangka Belitung region, operates 9 generator units and 9 voltage step-up transformers. The output voltage will be supplied through the 150 kV SUTT. In this study, transient stability will be analyzed in the condition of 9 generators operating at PLTD Merawang. Transient analysis was performed using the Runge-Kutta method. When the 9 PLTD Merawang generators were operating, the fastest critical disconnection time was 0.11 seconds, which resulted in a 3-phase fault on the line at point D, the line at point E, and the line at point F.